The New Novel / A New Novel: Spider's Webs and Detectives in Luisa Valenzuela's Black Novel (with Argentines) - Sharon Magnarelli (Studies in 20th & 21st Century Literature, 1995)
The article analyzes Valenzuela's novel in relation to Shaw's summary of projections about the directions the new novel will or should take. Specifically, it examines the novel in terms of the detective novel to which the title alludes and demonstrates that Valenzuela departs from the traditional detective novel with its quest for knowledge. In Valenzuela's novel there are no definitive answers, only obscurely intuited connections, which we would perhaps prefer not to make, for Valenzuela eschews both a master narrative and a narrative of mastery. Nonetheless, as the article demonstrates, the protagonists' search for motives, their quest to understand the gratuitous violence of Augustin's murder of an actress whom he had just met, is directly related to the desire to understand the sociopolitical events—the terror and violence—in Argentina during the late 1970s and early 1980s.
Keywords: Luisa Valenzuela; detective novel; knowledge; narrative; violence; terror; Argentina; Post-Boom; Argentine literature